PERAN PASAR TRADISIONAL DALAM MENYERAP ANGKATAN KERJA PEREMPUAN - Siti Inayatul Faizah (Faculty of Economics, Universitas Islam Indonesia, 2011)
Imbalancing between over labor with ability of absorption capacity happened in a long time. Since the construction decade era 1970’s had signed by labor problem (unemployment). The construction that wasn’t on proletariat’s side can be one of because rooted jobless problem. The construction program also became drift of citty and man caused happening of difference between man and women laborer was very significant. Drift of construction that caused difference between man and woman laborer, had effect on status movement of woman laborer. Gradually, it was true that there were rising Participation of Labor Generation Level (TPAK) of woman. But if we studied more trhough percentage comparison of Participation Labor Force Level (TPAK) of woman to woman citizen from the whole, it gave the low result. Based on quantity, infact the woman laborer had big potential was neglected and let trhough, it will have negative effect on acceleration of economy growth and development of construction process. According to SUSKERNAS notes, rising of Participation Labor Force Level (TPAK) of woman before crisis in 1980s era was absorbed in industry sector. But, the top of storm crisis in 1997 caused mass decrease in the labor world and Participation Labor Force Level (TPAK) of woman in this sector has gone down. As alternative, the over woman laborer lean expectation and their life on informal sector traditional market. This sector became main alternative because its characteristic that was flexible to accept whoever without seeing on gender, capital, skill and the access of labor information.